2020
DOI: 10.2147/dmso.s246743
|View full text |Cite
|
Sign up to set email alerts
|

<p>Activation of Nrf2 Signaling by Apelin Attenuates Renal Ischemia Reperfusion Injury in Diabetic Rats</p>

Abstract: Objective: Renal ischemia/reperfusion (I/R) injury is commonly seen in diabetic patients. Apelin has been demonstrated to protect against renal I/R injury, whereas detailed modulatory mechanisms by which Apelin exerts its role in renal I/R injury in diabetic patients remain unclarified. This research aimed to probe the functional molecules under the regulation of Apelin in renal I/R injury in diabetic rats. Materials and Methods: First, animal models were established for subsequent assays. Biochemical kits mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(34 reference statements)
0
10
0
1
Order By: Relevance
“…It has also been reported that apelin inhibited renal dysfunction in adenine-induced chronic renal failure in rats ( Abul-fadle, Saied & Musa, 2018 ) and podocyte autophagy in diabetes ( Liu, Zhang & Wang, 2017 ). Furthermore, apelin ameliorated the affected renal function and histological structure, decreased inflammatory mediators and ROS, and hampered cell apoptosis in renal ischemia/reperfusion injury ( Bircan et al, 2016 and Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 98%
“…It has also been reported that apelin inhibited renal dysfunction in adenine-induced chronic renal failure in rats ( Abul-fadle, Saied & Musa, 2018 ) and podocyte autophagy in diabetes ( Liu, Zhang & Wang, 2017 ). Furthermore, apelin ameliorated the affected renal function and histological structure, decreased inflammatory mediators and ROS, and hampered cell apoptosis in renal ischemia/reperfusion injury ( Bircan et al, 2016 and Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 98%
“… 19 , 20 Previously, regulating Nrf2 and its downstream genes could decrease inflammatory factor release, reduce oxidative stress, and maintain anti-apoptotic and survival abilities in the injured kidney. 21 Therefore, restraining oxidative stress through activating Nrf2 pathway might be a possible therapeutic strategy targeting sepsis-related AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, levels of apelin were altered in many disease models. For example, Zhang et al (2020) reported that Apln mRNA level increases both in the renal cortex and medulla in diabetic rats with renal ischemia-reperfusion injury, and apelin expression was significantly downregulated in pulmonary arterial hypertension and heart failure ( Yang et al, 2015 ). We previously reported that renal Apln mRNA expression was controlled by (pro)renin receptor (PRR) and significantly downregulated in high-salt-fed Dahl salt-sensitive rats ( Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%